River Cities in Asia Waterways in Urban Development and History - Padawangi, Rita; Rabé, Paul; Perkasa, Adrian (Asian Cities, 2022)
River Cities in Asia uncovers the intimate relationship between rivers and cities in Asia from a multi-disciplinary perspective in the humanities and the social sciences. As rivers have shaped human settlement patterns, economies, culture and rituals, so too have humans impacted the flow and health of rivers. In Asia, the sheer scale of urbanization increases the urgency of addressing challenges facing urban rivers, leading to the importance of historically, socially, and culturally relevant solutions. However, cities are also uneven landscapes of power, affecting chances to achieve holistic ecological approaches. The central premise of River Cities in Asia is that a "river city" is one where proximity between a river and a city exists across time and space, natural and social dimensions. Recognition of these deep connections can help to better contextualize policy solutions aimed at rivers and their ecologies, including human life.